1978
DOI: 10.1007/bf02885576
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of photo-inducedTrichoderma viride conidiation by inhibitors of RNA synthesis

Abstract: The photo-induced conidiation of Trichoderma viride is suppressed by ethidium bromide, acriflavin, lomofungin and 8-quinolinol at concentrations which do not inhibit the colony growth of this deuteromycete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…RNA synthesis inhibitors added after 7 h had no effect on conidiation. Protein synthesis inhibitors have also been shown to inhibit conidiation (Betina & Zajacová, 1978b). Together, these results clearly demonstrate that de novo transcription and translation are required during photoconidiation from at least 3 h and up to 7 h post light exposure.…”
Section: Lightmentioning
confidence: 61%
“…RNA synthesis inhibitors added after 7 h had no effect on conidiation. Protein synthesis inhibitors have also been shown to inhibit conidiation (Betina & Zajacová, 1978b). Together, these results clearly demonstrate that de novo transcription and translation are required during photoconidiation from at least 3 h and up to 7 h post light exposure.…”
Section: Lightmentioning
confidence: 61%
“…3). As might be expected, protein synthesis inhibitors also block conidiation (Betina & Zajacová, 1978). In early studies it was shown that light-induced conidiation is inhibited in hyphal cells which develop in the absence of oxygen (Gutter, 1957).…”
Section: Light Perception and Gene Expression At Early Stages Of The mentioning
confidence: 79%
“…This developmental programme can be divided into a determination state and a morphogenetic stage that includes reprogramming of gene expression, and the appearance of the corresponding physiological and morphological changes. Accordingly, the operation of this programme can be suppressed using RNA synthesis inhibitors, once it has been triggered by light, but only in a time window of approximately 7 h after illumination (Galun & Gressel, 1966;Gressel & Galun, 1967;Betina & Zajacová, 1978) (Fig. 3).…”
Section: Light Perception and Gene Expression At Early Stages Of The mentioning
confidence: 99%
“…The first indirect implication of nucleic acid involvement came from studies using the inhibitors 5-fluorouracil and 8-azaguanine (cf. GRESSEL andGALUN 1967, BETINA andZAJACOVA 1978). Fluorouracil and azaguanine completely suppressed sporulation with hardly measurable effects on growth.…”
Section: Transcription/translationmentioning
confidence: 97%